Performance and Quality of Broiler Meat During Transportation with Various Durations and ZnSO4 level - Dhini Nova Widyasari; Niken Ulupi; Rudi Afnan; Rita Mutia; Jonathan Anugrah Lase (Buletin Peternakan, 2021)
Heat stress in the poor transportation systems will impact the oxidative stress, affecting the quality of chicken meat. The decrease in heat stress levels can be trigerred through antioxidants, one of which is ZnSO4 antioxidants, before cutting. This study aimed to examine the reduction of post-transport stress on the performance of chickens, carcasses, and the physical and chemical qualities of broiler meat treated with ZnSO4. The total broiler chickens transported were 324 roosters aged 4 weeks (with 3 replicates each). All of the transported chickens were treated with ZnSO4 at doses of 0, 80, and 160 ppm for 7 days. Next, the chickens were transported with a travel time of 1, 2, and 3 hours. The breast meats were taken (filet) to be used as research samples. A factorial randomized block design was used as the research design and the data were analyzed using ANOVA (analysis of variance). The results showed that there was no correlation between travel time and the ZnSO4 levels on broiler chicken performance (weight and carcass loss) and physicochemical quality of broiler meat (pH value, percentage of water lost, aw, cooking loss, glycogen content and MDA). Longer travel time significantly reduced live weight, carcass percentage, pH value, glycogen content, while increasing the MDA levels. The addition of ZnSO4 can significantly increase the pH value of breast meat, maintain high glycogen levels, increase carcass percentage, and inhibit MDA formation.